The transcription factors regulating intervertebral disc development - Nakamichi, Ryo (JOR Spine, 2020)
Damage to the intervertebral discs (IVDs) occurs due to aging or excessive mechanical stress, causing a series of IVD‐related degenerative diseases, such as spinal disc herniation and spondylosis. These IVD‐related diseases are difficult to cure, partially because the regeneration ability of IVDs is not sufficient. As a novel strategy for treatment of IVD‐related diseases, mesenchymal stem cell transplantation to the damaged discs has been reported in animal studies. To further develop and improve this approach, it is necessary to gain a better understanding of the molecular network regulating IVD development by critical transcription factors. Recent findings reveal that during IVD development, nucleus pulposus and annuls fibrosus differentiation is coordinated by a series of transcription factors, such as Mkx, Pax1, 9, Shh, Foxa1, 2, T‐Brachyury, and Sox5, 6, 9. The combination of mesenchymal stem cell transplantation with the regulation of these molecules may provide a novel strategy for treatment of degenerative disc diseases.